Uluborlu’daki Türkiye Selçuklu ve Hamidoğulları Dönemine Ait Kitabelerin İnceleme ve Değerlendirilmesi. - Bakır, Abdullah; Demir, Fatih (Electronic Turkish Studies, 2023)
The place where the epigraphic works that are the subject of our study are located is the Uluborlu district of Isparta. Its first conquest took place in the period of 1075, during the reign of the Seljuk ruler Süleymanşah. Later, it came under Byzantine rule again in 1120, but in 1180 it was finally turned into Seljuk territory by Sultan Kılıçarslan II. Until that day, the city, which was known by names such as Apollonia, Mordiaum and Sozopolis, was given the name Borgulu by the Seljuks. Due to its geographical location, being at an important point of military and commercial roads and its castle being in a safe location, some of the Seljuk family settled in Uluborlu castle and after that the city became an important center for the Türkiye Seljuks. With the migrations they received later, important scholars and craftsmen settled here, and subsequently, scientific, cultural and industrial institutions emerged in the city. Due to this importance, Sultan Kılıçarslan II appointed Gıyaseddin Keyhüsrev I as the administrator of the city of Uluborlu while he was dividing the country among his eleven sons. With the effect of the appointment of Keyhüsrev I to Uluborlu as the administrator, it became an important science and culture city of the Türkiye Seljuks. In addition, the city became the education and settlement place of the Türkiye Seljuk princes. The city maintained its importance during the period of principalities and became the place of establishment of Hamidids. Thus, Uluborlu became one of the most important cities of the region, which continued its importance in the period of Türkiye Seljuks, principalities and Ottomans. For this reason, many important scientific and cultural artifacts were built in the city during the Türkiye Seljuk and principalities period. During these reconstruction activities, many structures that remained from previous civilizations were either transformed or preserved as they are. During the surveys and scientific studies we carried out about the Middle Ages in the region, epigraphic works in architectural structures were examined and evaluated. Alaaddin Mosque construction and repair inscriptions and Great Fountain inscriptions are among the inscriptions that have survived to the present day from the Türkiye Seljuk period. The inscriptions of Efendi Sultan Mosque, Sheik Muhiddin (Miyedin) Fountain and Ahi Şemseddin Tomb are important inscriptions from the Hamidids period. In this context, seven inscriptions related to our subject were evaluated. These inscriptions have been studied in different scientific studies over time. However, in the examinations we made on the inscriptions, some erroneous information was detected and re-evaluated and the results were tried to be brought to the science of history. Thus, unknown and some missing information about the historical subjects in the inscriptions were determined. With this information, it is aimed to contribute to the scientific community. In our epigraphic studies, software that performs photogrammetric processing of digital images has been used. Thus, it was tried to capture the information about the surface texture that was overlooked in the inscriptions and to obtain better results in reading the inscriptions. Thus, better data can be obtained and evaluated at the stage of reading the inscriptions.